2015
DOI: 10.1021/am508812a
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Coils and Yarns of Polymeric Piezoelectric Nanofibers

Abstract: We report on highly stretchable piezoelectric structures of electrospun PVDF-TrFE nanofibers. We fabricated nanofibrous PVDF-TrFE yarns via twisting their electrospun ribbons. Our results show that the twisting process not only increases the failure strain but also increases overall strength and toughness. The nanofibrous yarns achieved a remarkable energy to failure of up to 98 J/g. Through overtwisting process, we fabricated polymeric coils out of twisted yarns that stretched up to ∼740% strain. This enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 43 publications
2
108
0
Order By: Relevance
“…In the future, electrospun polymer nanofiber yarns may enable a wide range of muscle hosts owing to their lower cost, high internal surface area, and large availability of functional polymers. For instance, electrospun fibers of piezoelectric poly(vinylidene fluoride trifluoroethylene) (PVDF-TrFE) have been demonstrated that can be twisted and coiled (50).…”
Section: Emerging Types Of Twisted Musclesmentioning
confidence: 99%
“…In the future, electrospun polymer nanofiber yarns may enable a wide range of muscle hosts owing to their lower cost, high internal surface area, and large availability of functional polymers. For instance, electrospun fibers of piezoelectric poly(vinylidene fluoride trifluoroethylene) (PVDF-TrFE) have been demonstrated that can be twisted and coiled (50).…”
Section: Emerging Types Of Twisted Musclesmentioning
confidence: 99%
“…1B and C, respectively. When the shaker was operating at 20 Hz with a force of 6 N and a strain of ~0.1%, the average values of V oc and I sc reached 3.8 V and 3.5 µA, respectively, which outperformed a number of reported PVDF-based NGs [6,30,32,33,36]. This superior performance was mostly attributed to the optimized device geometry and structural advantage of the mesoporous PVDF thin film.…”
Section: Resultsmentioning
confidence: 95%
“…Density functional theory has been used to calculate the piezoelectric coefficients and the full piezoelectric tensor for different copolymer configurations, also highlighting the role of shear forces contributions in flexible polymeric nanobeams . By using properly designed collectors, fibers can be arranged in various forms such as random mats, aligned strands, highly aligned arrays, ribbonds and yarns realized by twisting ribbons. Interesting, Baniasadi et al .…”
Section: Polymer‐based Ngsmentioning
confidence: 99%
“…have found that the twisting process of aligned ribbons of PVDF‐TrFE increases up to a factor of 2 the strain to failure, strength, and toughness of the materials. In addition, coils fabricated by twisting the yarns [Figure (a)] exhibit an additional enhancement of the strain to failure (by a factor 4 with respect to yarn) with a maximum strain up to ∼740% . Ribbons generate an output voltage of tens of mV under bending while the combination of the piezoelectric charges and friction under stretching are considered to contribute to the enhancement of the mechanical properties though the increase of shear and compressive forces between nanofibers.…”
Section: Polymer‐based Ngsmentioning
confidence: 99%